A GIS and remote sensing based modelling for landfill site selection: a case of City of Gweru, Midlands Province, Zimbabwe - Ndeke, Bruce (Midlands State University, 2018)
The aim of this study was to determine suitable sites for locating a landfill in Gweru city. The study also sought to analyze the social impacts of the current disposal site to the local residents. Interviews with the City of Gweru and EMA were used to get the results on the social impacts of the current disposal site. Questionnaires and observations were also used to complement the interviews. The impacts of the disposal site on soil quality was determined in this research. GIS and remote sensing were the major methods used in mapping the suitable areas as well as determining sampling points for soil quality tests. Multi criteria evaluation and weighted overlay analysis methods were used in landfill site selection process. Factors used for landfill site selection were: rivers, settlements, road, railway, airport, slope and soils. Results of the study shows that social problems such as diseases, odors, deterioration of living standards and reduction in the value of land are prevalent in woodlands park residential area as a result of the disposal site. Soil sample results shows that there is high concentration of chemical substances (lead 66.93 ppm, cadmium 1.27 ppm and sulphides 89.53 ppm) at the disposal as compared to the control sample concentration (lead 0.01ppm, cadmium 0.1ppm and sulphides 20.02ppm). A suitability map was generated showing 5 sites that are suitable for landfill siting in Gweru. Suitable area occupied only 2.7% whilst 97.3% of the land is unsuitable. It was recommended that Gweru city council should consider terminating its existing disposal site for an improved site from the possible suitable sites established by this study.